2014
DOI: 10.1016/j.cogdev.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a relation between executive function and pretense representation in preschool children

Abstract: Several theoretical formulations suggest a relation between children’s pretense and executive function (EF) skills. However, there is little empirical evidence for a correlation between these constructs in early development. Preschool children (N = 104; M age = 4-0) were given batteries of EF and pretense representation measures, as well as verbal, memory, and appearance-reality control tasks. Confirmatory factor analysis revealed two separable but overlapping aspects of EF (Conflict and Delay). EF was signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
93
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(107 citation statements)
references
References 77 publications
9
93
0
5
Order By: Relevance
“…Three other studies found a relationship to laboratory tests of knowledge about pretend play (Albertson & Shore, 2009;Carlson, White, & Davis-Unger, 2012;Kelly, Hammond, Dissanayake, & Ihsen, 2011); however, the knowledge tests themselves appear to require EF. What would be most telling is if engaging in pretend play were itself related to EF.…”
Section: Executive Functionmentioning
confidence: 89%
“…Three other studies found a relationship to laboratory tests of knowledge about pretend play (Albertson & Shore, 2009;Carlson, White, & Davis-Unger, 2012;Kelly, Hammond, Dissanayake, & Ihsen, 2011); however, the knowledge tests themselves appear to require EF. What would be most telling is if engaging in pretend play were itself related to EF.…”
Section: Executive Functionmentioning
confidence: 89%
“…Delay inhibition tasks (e.g., delay of gratification tasks) require children to control impulses or inhibit an automatic response in the context of a reward. Conflict EF tasks require children to suppress a dominant response while executing a novel, conflicting response and holding information in working memory (Carlson & Moses, 2001; Carlson, White, & Davis-Unger, 2014). Conflict EF tasks include Stroop-like inhibition tasks (e.g., day/night, bear/dragon) and attention shifting tasks (e.g., dimensional change card sort [DCCS]; Bernier et al, 2010; Carlson & Moses, 2001; Carlson et al, 2004; Matte-Gagné & Bernier, 2011).…”
Section: Executive Function Processesmentioning
confidence: 99%
“…Inhibitory control has previously been associated with performance on appearance-reality and false-belief tasks (e.g., Carlson, Moses, & Claxton, 2004;Leslie & Polizzi, 1998;Leslie, German & Polizzi, 2005), pretense (Carlson, White, & Davis-Unger, 2014) or judgment of emotional states (Bull, Phillips, & Conway, 2008), suggesting that it is conductive to suppressing one's current knowledge about reality or known facts. However, the role of inhibitory processes in perspective taking has rarely been investigated.…”
Section: Running Head: Spatial Perspective Taking and Inhibitory Contmentioning
confidence: 99%